2018
DOI: 10.1016/j.jid.2018.03.1304
|View full text |Cite
|
Sign up to set email alerts
|

1288 Dermatosis papulosa nigra: A quality of life survey study

Abstract: Stem cell factor (SCF) is developmentally critical for melanocyte migration, differentiation, and survival. Recently, SCF expression in hair shaft progenitor cells has been shown to be absolutely required for the pigmentation in hair shafts, as evidenced by the complete loss of hair pigmentation in mice without SCF in these epithelial cells. Interestingly, this fully disruption of hair pigmentation only targets melanogenic mature monocytes in the upper hair bulb, but not melanocyte precursors below. This shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Hence, a larger prospective sample size using DPN subjects at other geographical areas is warranted to confirm our findings. Sun exposure associated with occupation or outdoor occupation has been widely acclaimed as a potential risk factor for the development of pterygium compared with indoor occupation (9,14,17,19,20). Observed results from our study also confirm the higher risk of developing pterygium with chronic exposure to sun outdoors compared to indoor occupation.…”
Section: Multivariate Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…Hence, a larger prospective sample size using DPN subjects at other geographical areas is warranted to confirm our findings. Sun exposure associated with occupation or outdoor occupation has been widely acclaimed as a potential risk factor for the development of pterygium compared with indoor occupation (9,14,17,19,20). Observed results from our study also confirm the higher risk of developing pterygium with chronic exposure to sun outdoors compared to indoor occupation.…”
Section: Multivariate Analysissupporting
confidence: 78%
“…Age group, complexion and sun exposure were significantly associated with the incidence of pterygium in the facial DPN subjects. Previous studies have shown that age group (9,17), skin colour (14) and sun exposure (9,18) are associated with pterygium. This observation could partly be explained by the fact that cumulative UV exposure have been consistently linked with DPN (6) and pterygium (9,19), and both lesions tend to occur in adults with incidence increasing with age.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…Dermatosis papulosa nigra has a strong family history. 19 Telogen effluvium is a condition with hair fall followed by acute stress. Hair loss due to telogen effluvium is seen in post-COVID patients.…”
Section: Discussionmentioning
confidence: 99%
“…DPN is found more often in African American, East Asian, and South Asian populations (Fitzpatrick IV-VI) with a consistently reported predominance in women and is thought to be underrecognized [33][34][35][36]. There is a high likelihood of family history, especially in individuals with large numbers of lesions [37][38][39][40][41]. Autosomal dominant inheritance with incomplete penetrance has been proposed [11,40,42].…”
Section: Epidemiologymentioning
confidence: 99%